146k views
1 vote
2(3x + 6) = 3( x - 9)​

User Estanford
by
4.6k points

2 Answers

3 votes

Answer:

x= - 13

Explanation:

2(3x+6) = 3(x-9)

6x+12 = 3x -27

-3x -3x

3x+12=-27

-12 -12

3x= -39

/3 /3

x= - 13

User Benoit Courtine
by
4.5k points
0 votes

Answer:

x = -13

Explanation:

2(3x + 6) = 3( x - 9)​

Distribute

6x +12 = 3x - 27

Subtract 3x from each side

6x-3x+12 = 3x-27-3x

3x+12 = -27

Subtract 12 from each side

3x+12-12 = -27-12

3x = -39

Divide by 3

3x/3 = -39/3

x = -13

User Taro Sato
by
4.2k points